Factors associated with HIV and syphilis screenings among pregnant women at first antenatal visit in Lusaka, Zambia - Davis, Rindcy (2020)
Objectives: To identify characteristics associated with obtaining HIV and syphilis screenings of pregnant women attending a first antenatal visit in Lusaka, Zambia. Results: Among 18,231 participants from April 2015 to January 2016, 95% obtained HIV screening, 29% obtained syphilis screening, and 4% did not obtain antenatal HIV or syphilis screenings. Divorced/separated women were associated with a moderate decrease in prevalence of obtaining HIV (adjusted prevalence ratio (aPR) 0.88, 95% confidence interval (95% CI) 0.82, 0.95) and syphilis (aPR 0.51, 95% CI 0.27, 0.96) screenings compared to married women. Women with previous pregnancies were associated with a slight decrease in prevalence of obtaining HIV screening (aPR 0.97, 95% CI 0.95, 0.99) compared to women without previous pregnancy. Older women ≥ 35 years were associated with a slight decrease in prevalence of obtaining HIV screening (aPR 0.96, 95% CI 0.92, 0.99) compared to younger women. The statistically significant differences were not of clinical relevance as defined by a proportional difference of 10 percent. Findings of this study show that a vast majority of pregnant women are obtaining HIV screenings but not syphilis screenings during first antenatal visit. Provision of antenatal HIV and syphilis screening at first visit is only weakly related to patient level factors.